2018
DOI: 10.21083/partnership.v13i1.4137
|View full text |Cite
|
Sign up to set email alerts
|

Canadian and South African Scholars’ Use of Institutional Repositories, ResearchGate, and Academia.edu

Abstract: Since their initial development in the early 2000s, institutional repositories (IRs) have proliferated around the globe. Due to low faculty participation, however, content recruitment has often posed a significant challenge for librarians and others promoting their use. Through the last decade, academic social networks (ASNs), such as ResearchGate and Academia.edu, have become popular among scholars as a means to communicate with each other and share their research. Semi-structured interviews were conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…According to Abdelrahman (2015) the success of IRs in Sudan is attributed to effective collaboration between librarians, IT/information systems professionals, and engineers. Scott and Swanepoel (2018) believe that institutional policies and the efforts of library staff have a significant effect on the success of IRs in South Africa. They indicated that the University of Pretoria adopted a policy mandating both faculty members and students submit their peer-reviewed articles and published conference papers to the repository, this policy was well regarded.…”
Section: Discussionmentioning
confidence: 99%
“…According to Abdelrahman (2015) the success of IRs in Sudan is attributed to effective collaboration between librarians, IT/information systems professionals, and engineers. Scott and Swanepoel (2018) believe that institutional policies and the efforts of library staff have a significant effect on the success of IRs in South Africa. They indicated that the University of Pretoria adopted a policy mandating both faculty members and students submit their peer-reviewed articles and published conference papers to the repository, this policy was well regarded.…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that most of the European and US higher educational institutions had an institutional RG profile (Lepori et al , 2018). Scott and Swanepoel (2018) explored the views and practices of scholars at six universities in Canada and South Africa relating to institutional repositories and academic social networks. The study found that more than half of the scholars were active users of either RG or Academia.edu.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, scholars appreciated academic social networks both as a means of sharing their researches and as tools facilitating connections with their colleagues globally. Significantly, academic social networks were more popular among South African than Canadian researchers (Scott and Swanepoel, 2018). Muscanell and Utz (2017) examined the usage and usefulness of RG by American and European academics and analyzed the effects of usage on career outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%